Study of turbulence induced orbital angular momentum channel crosstalk in a 1.6km free-space optical link - Lavery, Martin P.J.; Heim, Bettina; Peuntinger, Christian; Magaña-Loaiza, Omar S.; Karimi, Ebrahim; Bauer, Thomas; Banzer, Peter; Marquardt, Christoph; Willner, Alan E.; Boyd, Robert W.; Padgett, Miles J.; Leuchs, Gerd (CLEO: Science and Innovations, CLEO-SI 2015, 2015)
We experimentally study the turbulence induced crosstalk between orbital angular momentum channels transmitted over a 1.6 km optical link. Our presented results indicate that turbulence mitigation techniques will be required for links of this length. © OSA 2015.
CRIS-Team Scopus Importer:2022-06-05